Interferon-γ and tumor growth - A. L. Ilyushin; I. V. Bogdashin; A. Z. Aleksanyan; V. V. Novikov; L. A. Ashrafyan (Сибирский онкологический журнал, 2023)
Purpose of the study: to analyze published data on the mechanisms of action of interferon gamma (IFN-γ) in tumor growth and to evaluate the possibility of its use in the treatment of solid tumors. Material and Methods. More than 200 publications were found in the Scopus, Pubmed, eLibrary and other databases, the search keywords were: interferon gamma, tumor growth, cancer therapy. This review includes 54 papers. Results. IFN-γ is a pleiotropic cytokine with antiviral, antitumor, and immunomodulatory functions and plays an important role in coordinating the innate and adaptive immune response. The success of immuno-oncology drugs and chemotherapy in the treatment of malignant tumors depends on the stimulation of the production and adequate signaling of IFN-γ. Suppression and loss of IFN-γ receptor and downstream signaling mediators, and amplifcation of molecules that inhibit the IFN-γ signaling pathway are common mechanisms for tumor cells to escape from the immune system. The development of malignant processes is accompanied by a change, more often a decrease, in the secretion of IFN-γ, which attracts the attention of researchers to its exogenous administration. Determination of the IFN-γ signature may be a predictive marker of clinical response to anticancer drug therapy. The antitumor properties of IFN-γ are largely dose-dependent, which has been clearly shown in clinical and experimental studies. Low doses of the drug often promote tumor growth. On the contrary, the use of high doses is usually accompanied by an antitumor effect. IFN-γ or its inducers remain promising agents for cancer therapy. Combinatorial strategies involving IFN-γ may be a rational option to overcome tumor resistance to blockade of immune checkpoints. Conclusion. It is necessary to continue fundamental and applied research to study the feasibility of using interferon gamma as a therapeutic agent in tumor growth.